How is the minimum wage shaping the wage distribution: minimum wage, spillovers, and wage inequality in Portugal - Oliveira, Carlos Brito Mascarenhas de (2021)
Over the last three decades, wage inequality and the importance of the minimum wage presented a nearly symmetric behavior in Portugal. Applying a semiparametric approach, this paper presents significant visual and quantitative evidence of how the MW structurally reshaped the wage distribution. The remarkable rise in the real MW of 2006-2019 explained virtually all of the decline in wage inequality, and 40% of the average wage growth, mostly driven by spillovers, which cascaded way above the minimum. The MW was most important for women, although spillovers were greater for men. Exploring the total-base wage differential also uncovered important new insights.